Razrabotka i adaptacija metodiki stimuljacii processov nejroplasticnosti mozga vysokokvalificirovannych sportsmenov - Nazarov, K. S.; Gorovaja, A. E.; Mitin, I. N.; Žolinskij, A. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
This paper presents results of the development and adaptation neuroplasticity-stimulated technique using ideomotor training. Electroencephalography (EEG) was used to indicate neuroplasticity-dependent reorganization. The approbation was carried out with participate of 18 National Team athletes, which was divided into 2 groups: control and experimental. Participants of control group were studying ideomotor training before and had the experience of its using, while the experimental group was studied for the first time. During the experiment ideomotor image was gradually getting more complicated in accordance with developed program. On stages of research, corresponding to different extend of forming of ideomotor training skill and addition into ideomotor image new modalities, was carried out the EEG-registration in order to reveal neuroplastic reorganization. Coherence analysis allowed to establish rebuildings of functional systems in a EEG channels, reflecting the functioning of ideomotor acts. There was found a dynamic of increase of cross-hemisperian synchronization of brain processes in majority of channels on before and after experimental intervention. Also, there was obtained data illustrating brain structure level synchronization before in after introduction of kinesthetic component in the training. It turns out that addition of kinesthetic modality leads to synchronization of motor cortex in mu-rhythm band. Summarizing, EEG-analysis proved efficiency of using developed method in the field of sport practice.